Pemahaman Warga Pedesaan Terhadap Perkembangan Psikologi Anak Anak - Uyun, Aip Syepul (Ma'soem University, 2021)
Parenting education is a fundamental knowledge for everyone to understand. Unfortunately parenting is still a topic that is rarely discussed, especially for those who stay in rural areas. Even though there are many mistakes in parenting styles that can very often happen to those, the low level of education and the lack of access provided by the government are the main reasons why parenting education is rarely accepted by villagers. This situation has a major influence on the low understanding of the community members of the knowledge of parenting. In addition, residents' understanding of the characteristics of child development is also very low. Providing facilities to carry out parenting seminars is one way to break this misunderstanding.